Characterizing and Assessing Innovation Platforms in Central and West Asia and North Africa - M. Oumer, Ali; Dhehibi, Boubaker; Akramov, Kamiljon; Al-Zu'bi, Maha; Baum, Michael (International Center for Agricultural Research in the Dry Areas, 2023)
Innovation platforms (IPs) can provide a multidisciplinary research environment to test outcome-oriented research/ scientific ideas, technologies, and innovations. These are particularly effective when agrifood challenges require cross-sectoral solutions and joint efforts of stakeholders who have a stake in both the problem and solution. IPs allow stakeholders to experiment together and share knowledge, resources, benefits, and risks for issues they cannot solve on their own, and benefit from the synergistic effects of working together. IP functions include innovations relating to technology, capacity development, organization, policy, institutional governance, and the integration of these dimensions. Contemporary tools of monitoring, evaluation, and learning (MEL) can be used to assess the IPs’ contribution to these dimensions and generate lessons for future scaling. Three aspects of the IPs can be monitored and evaluated. These are activities, process changes, and results generated by the IP for beneficiary groups. The member stakeholders or a designated sub-team should define the indicators and rubric thresholds to measure these changes. The International Centre for Agricultural Research in the Dry Areas (ICARDA) can upgrade its research stations into National Innovation Platforms (NIPs) by engaging diverse partners and stakeholders to jointly identify their challenges and test their innovations to address those challenges. For example, improved varieties of cereals and forages could be entry points to set up NIPs in these research stations. ICARDA’s country offices may be able to characterize the research stations and take the initiative to set up a NIP. The characterization and assessment of the research stations can proceed with the involvement of key stakeholders, including policymakers and the private sector.